New Studies in Dogmatics : The Holy Spirit - Holmes, Christopher R. J. (Zondervan, 2015)
Who is the Holy Spirit and how does the Spirit come to be in relation to the Father and the Son? What is the mission of the Spirit and where does it come from? Chris Holmes takes up the questions surrounding the Spirit’s procession and mission with the help of three of the church’s greatest teachers—Augustine, Thomas Aquinas, and Karl Barth. Drawing on their engagements with the Fourth Gospel, Holmes presents an account of the Spirit’s identity, origin, and acts, to show how the acts of the Spirit derive from the Spirit’s life in relation to Father and Son—and the extent to which the Spirit’s mission testifies to the Spirit’s origin. Holmes presents a way forward for pneumatology. Housed within the doctrine of the Trinity, pneumatology’s joyful task is to describe the Spirit’s acts among us in light of their source in the Spirit’s acts in God. The end of this inquiry is our beatitude—knowledge of the Trinity that yields to love of the Trinity. -ABOUT THE SERIES- New Studies in Dogmatics seeks to retrieve the riches of Christian doctrine for the sake of contemporary theological renewal. Following in the tradition of G. C. Berkouwer's Studies in Dogmatics, this series provides thoughtful, concise, and readable treatments of major theological topics, expressing the biblical, creedal, and confessional shape of Christian doctrine for a contemporary evangelical audience. The editors and contributors share a common conviction that the way forward in constructive systematic theology lies in building upon the foundations laid in the church's historic understanding of the Word of God as professed in its creeds, councils, and confessions, and by its most trusted teachers.